2005
DOI: 10.1302/0301-620x.87b1.14678
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the dog as a model for human total hip replacement

Abstract: Post-mortem retrieval of canine, cemented femoral components was analysed to assess the performance of these implants in the dog as a model for human total hip replacement (THR). Mechanical testing and radiological analysis were performed to determine the stability of the implant and the quality of the cement. Thirty-eight implants from 29 dogs were retrieved after time intervals ranging from 0.67 to 11.67 years. The incidence of aseptic loosening was 63.2%, much higher than in human patients (6% in post-morte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Our steady‐state wear rate of 0.99 mg/Mc is 2.4× less than a study by Saikko et al that examined gamma cross‐linked polyethylene in human THA (irradiation dose = 95 kGy). We would have expected a greater difference in wear rates, since canine implants experience approximately 10× less load than human implant wear tests, and a previous study of postmortem‐retrieved canine hip implants found the volumetric wear rates of conventional polyethylene liners are 10× greater in humans than in canines . A potential explanation for the relatively high wear results in our study is that the surface roughness of our femoral head components ( R a = 0.77 μm; Fig.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Our steady‐state wear rate of 0.99 mg/Mc is 2.4× less than a study by Saikko et al that examined gamma cross‐linked polyethylene in human THA (irradiation dose = 95 kGy). We would have expected a greater difference in wear rates, since canine implants experience approximately 10× less load than human implant wear tests, and a previous study of postmortem‐retrieved canine hip implants found the volumetric wear rates of conventional polyethylene liners are 10× greater in humans than in canines . A potential explanation for the relatively high wear results in our study is that the surface roughness of our femoral head components ( R a = 0.77 μm; Fig.…”
Section: Discussionmentioning
confidence: 62%
“…We would have expected a greater difference in wear rates, since canine implants experience approximately 10Â less load than human implant wear tests, and a previous study of postmortem-retrieved canine hip implants found the volumetric wear rates of conventional polyethylene liners are 10Â greater in humans than in canines. 22,23 A potential explanation for the relatively high wear results in our study is that the surface roughness of our femoral head components (R a ¼ 0.77 mm; Fig. 1) was fifteen times greater than the standard roughness of femoral heads used in human studies (R a ¼ 0.05 mm).…”
Section: Canine Hip Resurfacingmentioning
confidence: 66%
See 1 more Smart Citation
“…In each dog, there was failure at the bone–cement interface and in 2 dogs fracture (structural failure) of the PMMA. Furthermore, aseptic loosening is one of the most commonly reported complications in cemented THA often leading to implant failure 5,29–31 …”
Section: Discussionmentioning
confidence: 99%
“…To date, the availability of bone cements has been limited to non-resorbable materials that are comprised of polymethylmethacrylate, used commonly for the cementation of implants such as total hip replacements (22,23). Infection (24) and adhesive failure (25) are inherent risks with materials not removed or resorbed.…”
Section: Introductionmentioning
confidence: 99%